SEJARAH INDUSTRI SULAMAN INDAH MAYANG DI NARAS KOTA PARIAMAN TAHUN 2002-2015 - Susilawati Susilawati (UIN Imam Bonjol Padang, 2018)
Embroidery, the art of forming decorative designs with hand, has been aroundnearly as long as clothing itself. As a country full with diversity and enhanced withIndonesian creativity, the traditional touch in every product has made each of thema masterpiece. One of them, the embroidery which has been spreading inMinangkabau region, including Naras area as a center for embroidery City ofPariaman, is well-known as Sulaman Indah Mayang industry, which was foundedin 2012 by Fitrinawati. This industry was founded with the potential of embroiderypossessed by the Naras's people. Most interestingly, there were many jobopportunities especially for women and the desire of the people to preserve theirlocal cultural wealth. This study was conducted using descriptive qualitatitvemethod to see the history of the Sulaman Indah Mayang industry in Naras .However, amid an onslaught of technology, although many of embroidery machinesentering Naras, the Sulaman Indah Mayang industry still prefers to maintain theembroidery of traditions, namely, the original inheritance of their ancestors. thisindustry is also evolving rapidly after being guided by the Department of Industryand Trade of Pariaman City.